2017
DOI: 10.1002/wene.270
|View full text |Cite
|
Sign up to set email alerts
|

Household electricity consumers’ incentive to choose dynamic pricing under different taxation schemes

Abstract: Dynamic pricing of retail electricity, as opposed to the widely applied average pricing, has often been proposed to enhance economic efficiency through demand response. The development of variable production from renewable energies and expectations about the installation of heat pumps and electric vehicles has now reinforced interest in flexible demand and dynamic pricing. With a roll‐out of smart metering one important technical hurdle is going to be cleared, and dynamic retail pricing may soon become an elig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In fact, a trade-off seems to exist between the complexity of the tariff model and the engagement of households in DR programs [58]. To further complicate things, the variable charge that depends on electricity consumed represents only 18% of the total electricity price 6 in addition to the reluctant switching contract behavior of Danish customers [60]. Therefore, even under the assumption of entirely rational and informed individuals, a weak price signal would likely not encourage consumers to shift demand from peak to off-peak time due to the small financial gains associated with an active response to the program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a trade-off seems to exist between the complexity of the tariff model and the engagement of households in DR programs [58]. To further complicate things, the variable charge that depends on electricity consumed represents only 18% of the total electricity price 6 in addition to the reluctant switching contract behavior of Danish customers [60]. Therefore, even under the assumption of entirely rational and informed individuals, a weak price signal would likely not encourage consumers to shift demand from peak to off-peak time due to the small financial gains associated with an active response to the program.…”
Section: Discussionmentioning
confidence: 99%
“…To help activate flexible demand and minimize distortions, Katz et al [60] suggested introducing a dynamic approach to levies and taxes to increase the incentive to respond by a factor of three in a Danish setting. The debate about the introduction of a dynamic electricity tax and an overall reduction of the electricity taxes has recently moved into the agenda of the Danish Ministry of Climate, Energy and Utilities [24].…”
Section: Discussionmentioning
confidence: 99%
“…In Denmark, any consideration regarding the size of the ratio between the off-peak and on-peak rates should consider that the electricity price paid by domestic customers is largely dominated by fixed per-unit elements [88]. Indeed, the debate about the introduction of a dynamic electricity tax (and an overall reduction in the electricity taxes) as an instrument to boost flexible demand has recently entered the agenda of the Danish Ministry of Climate, Energy and Utilities [89].…”
Section: Discussionmentioning
confidence: 99%
“…In this vein, the impact of the high electricity tax in Denmark has raised the attention from the Academia. The present fixed tax structure was identified as a factor potentially hampering the adoption of dynamic pricing schemes for the household customers, by hiding the price signal incentive for demand-side flexibility [44]. Likewise, the implementation of several dynamic residential electricity taxation schemes in Demark was investigated in [45], evincing the main trade-offs implied.…”
Section: The Uneven Impact Of Taxes On the Different Customer Segmentsmentioning
confidence: 99%